Characterization of MreCD in Streptococcus mutans - Victor Chan; Tessa Holcomb; Justin R. Kaspar; Robert C. Shields (Journal of Oral Microbiology)
Background Activities that control cell shape and division are critical for the survival of bacteria. However, little is known about the circuitry controlling these processes in the dental caries pathogen Streptococcus mutans.Methodology We designed experiments to characterize two genes, mreC and mreD, in S. mutans. Assays included cell morphology imaging, protein interaction analysis, transcriptomics, proteomics, and biofilm studies to generate a comprehensive understanding of the role of MreCD in S. mutansResults Consistent with mreCD participating in cell elongation, cells lacking these genes were found to be rounder than wild-type cells. Using bacterial two-hybrid assays, interactions between MreCD and several other proteins implicated in cell elongation were observed. Further characterization, using proteomics, revealed that the surface-associated proteome is different in mutants lacking mreCD. Consistent with these changes we observed altered sucrose-mediated biofilm architecture. Loss of mreCD also had a noticeable impact on bacteriocin gene expression, which could account in part for the observation that mreCD mutants had a diminished capacity to compete with commensal streptococci.Conclusion Our results provide evidence that cell elongation proteins are required for normal S. mutans physiology and establish a foundation for additional examination of these and related proteins in this organism.